Integrating Verbal and Visual Signs in Meaning Making: A Semiotic Analysis - Khadka, Thir Bahadur (Spectrum of Humanities and Social Sciences, 2025)
This study reports a semiotic analysis of the complementary role of verbal and visual signs in meaning making process. As a case study approach, it analyses a number of selected cases from different fields like education, advertisement and multimedia platform consisting both the signs. The analysis has been carried out with the use of Saussurean notion of semiotic analysis particularly the idea of signifier and signified. The findings show that verbal (words, language, text) and visual signs (images, symbols, colours) have complementary role as their integration helps not only in the production of a comprehensive and meaningful text but also in the process of its analysis. Beside producing impactful teaching and advertising materials, this integration helps to have engaging digital texts. Development of cognitive methods and guidelines regarding the better use of multimodal communication in different fields can help in the production and analysis of more nuanced and impactful texts or messages in the present era of ever-growing use of digital technology in communication.